Is "War" the Right Word? Cultured Meat and the Theory of "The War Against Animals" - Giles, Richard (Journal of applied animal ethics research, 2025)
Dinesh Joseph Wadiwel’s The War Against Animals, published in 2015, argues that human relations with the nonhuman other constitute a war, and must consequently be understood as such. In the ten years since the book’s publication, cultured meat has arisen as an alleged ethical and environmental victory, necessitating a critical attempt to reconcile its existence with Wadiwel’s thesis. This paper argues that, to understand cultured meat’s role in this war, one must first critique the concept overall, which is conducted through a comparison with Jean Baudrillard’s The Gulf War Did Not Take Place. Premised on the basis that Baudrillard’s work can help better accentuate the simulacrumatic elements of the war against animals, the paper ultimately argues that cultured meat does not resolve the war, but instead, moves the war against animals towards a more "virtual" stage. A more critical understanding of cultured meat, the war against animals writ large, and the terminology that is used, is essential to better diagnose cultured meat’s ethical implications for animals.